Sensory axon targeting is increased by NGF gene therapy within the lesioned adult femoral nerve - Hu, Xinhua (2009)
Even though peripheral nerves regenerate well, axons are often misrouted and reinnervate inappropriate distal pathways post-injury. Misrouting most likely occurs at branch points where regenerating axons make choices. Here, we show that the accuracy of sensory axon reinnervation is enhanced by overexpression of the guidance molecule nerve growth factor (NGF) distal to the bifurcation. We used the femoral nerve as model, which contains both sensory and motor axons that intermingle in the parent trunk and distally segregate into the saphenous (SB) and motor branch (MB). Transection of the parent trunk resulted in misrouting of axon reinnervation to SB and MB. To enhance sensory axon targeting, recombinant adenovirus encoding NGF was injected along the SB close to the bifurcation one week post-injury. The accuracy of axon reinnervation was assessed by retrograde tracing at 3 or 8 weeks after nerve injury. NGF overexpression significantly increased the accuracy of SB axon reinnervation to the appropriate nerve branch, in a manner independent of enhancing axon regeneration. This novel finding provides in vivo evidence that gradient expression of neurotrophin can be used to enhance targeting of distal peripheral pathways to increase axon regeneration into the appropriate nerve branch.